A micro-nano composite structure aluminum powder material, preparation method and application thereof

By depositing nano-aluminum powder in the electrical explosion chamber to form a micro-nano composite structure on the micro-aluminum powder, the problems of poor reaction activity of micro-aluminum powder and low energy of nano-aluminum powder are solved, and a lower starting reaction temperature and higher energy density, suitable for high-energy applications.

CN115446305BActive Publication Date: 2025-01-14XIAN MODERN CHEM RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210974523.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-15
Publication Date
2025-01-14
Estimated Expiration
2042-08-15

AI Technical Summary

Technical Problem

In the prior art, the micro-aluminum powder has poor reactivity and the absolute energy of nano-aluminum powder is low, resulting in the problem of difficulty in ignition and insufficient energy in practical applications.

Method used

The aluminum wire is fixed on the electrode in the electric explosion chamber, and the nano-aluminum powder particles are deposited on the circulating micro-aluminum powder particles through the electric explosion reaction, forming a micro-nano composite structure aluminum powder material with a mass ratio of 8:1 to achieve Multiscale structures of macroscopic microscale and microscopic nanostructures.

Benefits of technology

It significantly reduces the initial reaction temperature and combustion time, improves the reaction activity and energy density, and makes the combustion heat of micro-nano composite structure aluminum powder material more concentrated, and is suitable for the preparation of solid rocket propellants or high-energy explosives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115446305B_ABST
    Figure CN115446305B_ABST
Patent Text Reader

Abstract

The invention discloses a micro-nano composite structure aluminum powder material, a preparation method and application. The preparation method comprises the following steps: fixing aluminum wire on upper and lower electrodes in an electric explosion chamber; sending a formulated amount of micron aluminum powder into the electric explosion chamber, then evacuating the electric explosion chamber to vacuum and filling it with argon gas, and adjusting the gas pressure to 0.1MPa-0.2MPa, so that the micron aluminum powder particles circulate in the electric explosion chamber; starting the electric explosion device, so that the nano aluminum powder particles generated by the electric explosion reaction are deposited on the micron aluminum powder particles circulating in the electric explosion chamber to obtain the micro-nano composite structure aluminum powder material. The micro-nano composite structure aluminum powder material finally obtained by the invention has a multi-scale structure of macroscopic micron scale and microscopic nanostructure, and the morphology is spherical, nearly spherical or quasi-spherical; the initial reaction temperature of the micro-nano composite structure aluminum powder material is 550°C, and the weight gain of the first oxidation reaches 38.4%, the reaction temperature and the initial reaction temperature are greatly reduced, the reaction activity is greatly improved, and the energy release process is more concentrated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials and relates to aluminum powder materials, and specifically to a micro-nano composite structure aluminum powder material, a preparation method and application thereof. Background Art

[0002] Aluminum has become the most widely used metal fuel due to its cost and energy advantages, but its own structural characteristics determine that it has some defects in practical applications. For example, Li ZY, et al. pointed out in the article "Effects of Particle Size on Two-Phase Flow Loss in Aluminized Solid Rocket" Motors[J]. Acta Astronaut., 2019, 159: 33-40: Affected by the size and structure of the material itself, the commonly used micron aluminum powder has a high effective aluminum content, but the ignition temperature is usually higher than 2000K. In the actual reaction process, the aluminum powder particles will undergo a melting-accumulation-agglomeration process from the time they are exposed to the propellant combustion surface. In this process, large aluminum droplets will be formed, making the ignition of aluminum difficult and the ignition temperature high. Gromov AA et al. pointed out in Metal nanopowder: production, characterization, and energetic application [M]. Wiley-VCH, Weinheim, 2014 that nano-aluminum powder has higher reactivity and reaction completeness, lower ignition temperature (800K), and shorter combustion time, which increases the thermal feedback to the reaction interface and can effectively reduce the two-phase flow loss. However, due to the special particle size of nano-aluminum powder, the effective aluminum (active aluminum) content decreases significantly with the decrease of particle size. Usually, the absolute energy of the material is somewhat different from that of micron aluminum powder due to the effective aluminum content of less than 90%. Summary of the invention

[0003] In view of the defects and shortcomings of the prior art, the purpose of the present invention is to provide a micro-nano composite structure aluminum powder material to solve the technical problem that the central micron aluminum powder in the prior art has poor reactivity and the nano aluminum powder has low absolute energy.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0005] A method for preparing a micro-nano composite structure aluminum powder material comprises the following steps:

[0006] Step 1, fix the aluminum wire on the upper and lower electrodes in the electric explosion chamber;

[0007] Step 2, feeding a formulated amount of micron aluminum powder into an electric explosion chamber, then evacuating the electric explosion chamber to a vacuum and filling it with argon gas, and adjusting the gas pressure to 0.1MPa-0.2MPa, so that the micron aluminum powder particles circulate in the electric explosion chamber;

[0008] Step 3, starting the electric explosion device to deposit the nano aluminum powder particles generated by the electric explosion reaction on the micron aluminum powder particles circulating in the electric explosion chamber to obtain a micro-nano composite structure aluminum powder material;

[0009] Among them, in the micro-nano composite structure aluminum powder material, the mass ratio of micron aluminum powder to nano aluminum powder is (8-10):1.

[0010] The present invention also has the following technical features:

[0011] Optionally, the shape of the micro-nano composite structure aluminum powder material is spherical, nearly spherical or quasi-spherical.

[0012] Furthermore, in the micro-nano composite structure aluminum powder material, the particle size distribution of the nano aluminum powder particles is 100-200 nm, and the particle size distribution of the micron aluminum powder is 8-12 μm.

[0013] Furthermore, in step 1, the diameter of the aluminum wire is 0.1 to 0.35 mm.

[0014] Furthermore, in step 3, the transmission rate of the circulating micron aluminum powder is 4g / min to 10g / min; the discharge voltage of the electric explosion reaction is 20 to 30KV, the capacitor capacity is 3.0 to 4.0μF, the discharge frequency is 0.5 to 1.5Hz, and the electric explosion length is 70 to 120mm.

[0015] Furthermore, in step 3, the time for the nano-aluminum powder particles to be deposited on the micron-aluminum powder particles is 30 to 60 minutes.

[0016] Furthermore, the preparation method comprises the following steps:

[0017] Step 1, fix the aluminum wire with a diameter of 0.2 mm on the upper and lower electrodes in the electric explosion chamber;

[0018] Step 2, 300g of micron aluminum powder with an average particle size of 10μm is fed into the electric explosion chamber, and then the electric explosion chamber is evacuated to a vacuum and filled with argon gas, and the gas pressure is adjusted to 0.1MPa, so that the micron aluminum powder particles circulate in the electric explosion chamber;

[0019] Step 3, starting the electric explosion device to deposit the nano aluminum powder particles generated by the electric explosion reaction on the micron aluminum powder particles circulating in the electric explosion chamber to obtain a micro-nano composite structure aluminum powder material;

[0020] Among them, in the micro-nano composite structure aluminum powder material, the mass ratio of micron aluminum powder to nano aluminum powder is 10:1; the particle size distribution of the nano aluminum powder is 100-200nm;

[0021] In the step 3, the transmission rate of the circulating micron aluminum powder is 5g / min; the discharge voltage of the electric explosion reaction is 25KV, the capacitor capacity is 3.6μF, the discharge frequency is 0.5Hz, and the electric explosion length is 100mm; the time for the nano aluminum powder to be deposited on the micro aluminum powder is 30min.

[0022] The present invention also protects a micro-nano composite structure aluminum powder material, and the composite material is prepared by the preparation method of the micro-nano composite structure aluminum powder material.

[0023] Preferably, in the micro-nano composite structure aluminum powder material, the mass ratio of micron aluminum powder to nano aluminum powder is 10:1;

[0024] The particle size distribution of nano aluminum powder particles is 100-200nm, and the particle size distribution of micron aluminum powder is 8-12μm.

[0025] The present invention also protects the use of the micro-nano composite structure aluminum powder material obtained by the preparation method of the above-mentioned micro-nano composite structure aluminum powder material for preparing solid rocket propellant or high-energy explosive; or the use of the above-mentioned micro-nano composite structure aluminum powder material for preparing solid rocket propellant or high-energy explosive.

[0026] Compared with the prior art, the present invention has the following technical effects:

[0027] (1) The micro-nano composite structure aluminum powder material prepared by the preparation method of the present invention has a multi-scale structure of macroscopic micrometer scale and microscopic nanostructure, and is spherical in shape. Nano aluminum powder particles with a particle size of 100 to 200 nm grow on the surface of aluminum powder with a particle size of 8 to 12 μm. Compared with micron aluminum powder, the initial reaction temperature of the micro-nano composite structure aluminum powder material is 550°C, and the weight gain of one oxidation reaches 38.4%. The reaction temperature and the initial reaction temperature are greatly reduced, the reaction activity is greatly improved, and the energy release process is more concentrated. The measured combustion heat of the micro-nano composite structure aluminum powder material is 26.3 KJ / g, while the measured combustion heat of the nano aluminum powder prepared by electric explosion is only 24.5 KJ / g. Compared with nano aluminum powder, the micro-nano composite structure aluminum powder material provided by the present invention has a higher energy advantage.

[0028] (2) The micro-nano composite aluminum powder material prepared by the preparation method of the present invention has a stable structure and can be used to prepare solid rocket propellants or high-energy explosives. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings are used to provide further understanding of the present disclosure and constitute a part of the specification. They are used to explain the present disclosure together with the following detailed description, but do not constitute a limitation of the present disclosure.

[0030] In the attached picture:

[0031] Figure 1 This is a scanning electron microscope image of the micro-nano composite structure aluminum powder material prepared in Example 1;

[0032] Figure 2 This is a particle size distribution diagram of the micro-nano composite structure aluminum powder material prepared in Example 1;

[0033] Figure 3 This is the XRD pattern of the micro-nano composite structure aluminum powder material prepared in Example 1;

[0034] Figure 4 This is the DSC-TG graph of the micro-nano composite structure aluminum powder material prepared in Example 1.

[0035] The specific contents of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by any ordinary technician in the field belong to the scope of protection of the present invention.

[0037] It should be noted that all raw materials, experimental equipment and testing equipment in the present invention, unless otherwise specified, are raw materials and equipment known in the art.

[0038] The technical concept of the present application is to provide a new powder processing technology, that is, to use an electric explosion device that can realize coaxial wire feeding and powder feeding, so that the aluminum vapor generated in the electric explosion process is deposited and wrapped on the surface of the micron aluminum powder, so that nano aluminum powder particles with a particle size of 100 to 200 nm grow on the surface of aluminum powder with a particle size of 8 to 12 μm, and finally obtain a micro-nano composite structure aluminum powder material with a multi-scale structure of macroscopic micrometer scale and microscopic nanostructure, thereby improving the material performance.

[0039] The present invention provides a method for preparing a micro-nano composite structure aluminum powder material, the method comprising the following steps:

[0040] Step 1, fix the aluminum wire on the upper and lower electrodes in the electric explosion chamber;

[0041] Step 2, feeding the formulated amount of micron aluminum powder into the electric explosion chamber, then evacuating the electric explosion chamber to vacuum and filling it with argon gas, and adjusting the gas pressure to 0.1MPa-0.2MPa;

[0042] When the electric explosion chamber is evacuated, a filter screen is arranged at the vacuum port opening, so that the input micron aluminum powder can be prevented from being drawn out of the electric explosion chamber along with the air.

[0043] Step 3, starting the electric explosion device to deposit the nano aluminum powder particles generated by the electric explosion reaction on the micron aluminum powder particles circulating in the electric explosion chamber to obtain a micro-nano composite structure aluminum powder material;

[0044] That is, the metal vapor generated by the electric explosion reaction is brought into contact with the micron aluminum powder flowing in the electric explosion chamber, the metal vapor is cooled to generate nano aluminum powder particles, and then the nano aluminum powder particles are deposited on the micron aluminum powder particles to obtain a micro-nano composite structure aluminum powder material;

[0045] Among them, in the micro-nano composite structure aluminum powder material, the mass ratio of micron aluminum powder to nano aluminum powder is (8-10):1.

[0046] The shape of the micro-nano composite structure aluminum powder material is spherical, nearly spherical or quasi-spherical.

[0047] In the micro-nano composite structure aluminum powder material, the particle size distribution of nano aluminum powder particles is 100-200 nm, and the particle size distribution of micron aluminum powder is 8-12 μm.

[0048] In step 1, the diameter of the aluminum wire is 0.1-0.35 mm.

[0049] In the step 3, the transmission rate of the circulating micron aluminum powder is 4g / min to 10g / min; the discharge voltage of the electric explosion reaction is 20 to 30KV, the capacitor capacity is 3.0 to 4.0μF, the discharge frequency is 0.5 to 1.5Hz, and the electric explosion length is 70 to 120mm.

[0050] Compared with micron aluminum powder materials, the initial reaction temperature of micro-nano composite structure aluminum powder materials is 550°C, and the weight gain of one oxidation reaches 38.4% of the reaction temperature. The initial reaction temperature is greatly reduced, the reaction activity is greatly improved, and the energy release process is more concentrated.

[0051] The performance test instruments and models involved in the following experiments of the present invention are shown in Table 1:

[0052] Table 1

[0053] Instrument Name model Scanning electron microscopy (SEM) FEI Quanta 400ESEM-FEG X-ray diffraction (XRD) Japan Rigaku Corporation D / MAX-2400 Laser particle size analyzer Master saizer 2000 from Malvern, UK Differential Scanning Calorimetry-Thermogravimetric Analyzer (DSC-TG) German Netzsch company 204HP Oxygen bomb calorimeter Changsha Fantawild RF-C7000(TJZ)

[0054] DSC-TG: Take 0.05 g sample, the test heating rate is 20 ° C / min, the atmosphere is air.

[0055] XRD test: take 0.05g sample, use Cu Kα as the radiation source, graphite monochromator, test under the conditions of tube voltage of 40kV, tube current of 100mA, and scanning rate of 1.5° / min.

[0056] SEM test: stick a carbon conductive double-sided tape on the carrier plate, take a small amount of the sample to be tested on the tape, use a rubber ball to blow gently in the radial outward direction of the carrier plate to make the sample evenly distributed on the tape, then put it into the electron microscope cavity and measure it at a working voltage of 20kV.

[0057] Laser particle size test: Weigh 0.05 sample, disperse it in the test device, adjust the laser transmittance to 20%, and complete the test under stirring and ultrasound.

[0058] Oxygen bomb test: Weigh 0.5g of sample in a copper crucible, put it into an oxygen bomb, connect the ignition wire, fill it with oxygen to 3.0MPa, put the oxygen bomb into the test water bucket and ignite it to complete the combustion heat measurement.

[0059] Example 1

[0060] Step 1, fix the aluminum wire with a diameter of 0.2 mm on the upper and lower electrodes in the electric explosion chamber;

[0061] Step 2, 300g of aluminum powder with an average particle size of 10 microns is loaded into the electric explosion chamber, the system is evacuated and filled with argon gas, and the gas pressure is adjusted to 0.1MPa, and the gas circulation device is started to make the micron aluminum powder particles circulate in the electric explosion chamber of the electric explosion reactor;

[0062] Step 3, start the electric explosion device, control the transmission rate of the circulating micron aluminum powder to 5g / min, and complete the reaction under the conditions of a discharge voltage of 25KV, a capacitor capacity of 3.6μF, a discharge frequency of 0.5Hz, an electric explosion length of 100mm, and a deposition time of 30min, so that the nano aluminum powder particles produced by the electric explosion reaction are deposited on the circulating micron aluminum powder particles in the electric explosion chamber to obtain a micro-nano composite structure aluminum powder material. During the reaction, the consumption mass of the aluminum wire is 37.5g.

[0063] The prepared samples are collected to become micro-nano composite structure aluminum powder materials.

[0064] The performance characteristics of the micro-nano composite structure aluminum powder material of the present invention are as follows:

[0065] SEM observations showed that the micro-nano composite aluminum powder prepared by electric explosion deposition reaction was spherical with uniform particle size, and nanoparticles with a particle size of 100 to 200 nm were wrapped on the surface of the micron aluminum powder, eventually forming a micro-nano composite structure.

[0066] The results of laser particle size test show that the particle size distribution of the prepared micro-nano composite structure aluminum powder material is bimodal, with the particle size peak of 100-200nm corresponding to nanoparticles and the particle size peak of 8-12 microns corresponding to micron particles.

[0067] The XRD test of the micro-nano composite structure aluminum powder material shows that the micro-nano composite structure aluminum powder is mainly composed of single element aluminum, and no diffraction peaks of other phases are observed.

[0068] The DSC-TG test of the micro-nano composite structure aluminum powder material in air atmosphere shows that the initial oxidation temperature of the micro-nano composite structure aluminum powder is 550℃, the oxidation peak temperature is 600℃, there is only one oxidation peak, and the corresponding oxidation weight gain reaches 38.4%wt. Compared with the micron aluminum powder in the comparative literature, the oxidation peak temperature of the micro-nano composite structure aluminum powder is reduced by 400℃, and the oxidation weight gain is increased by 9%. There is no exothermic phenomenon in the subsequent test process, and the exothermic process is concentrated, which changes the exothermic process of the micron aluminum powder, indicating that the chemical energy of the micro-nano composite structure aluminum powder is all released in the front stage of the reaction.

[0069] The combustion heat test shows that the measured combustion heat of the micro-nano composite structure aluminum powder material is 26.3KJ / g, while the measured combustion heat of the nano aluminum powder prepared by electric explosion is only 24.5KJ / g. Therefore, compared with nano aluminum powder, the micro-nano composite structure aluminum powder material prepared by the method of the present invention has a higher energy advantage.

[0070] Example 2

[0071] Step 1, fix the aluminum wire with a diameter of 0.3 mm on the upper and lower electrodes in the electric explosion chamber;

[0072] Step 2, 400g of aluminum powder with an average particle size of 10 microns is loaded into the electric explosion chamber, the system is evacuated and filled with argon gas, and the gas pressure is adjusted to 0.15MPa, and the gas circulation device is started to circulate the micron aluminum powder particles in the electric explosion chamber of the electric explosion reactor;

[0073] Step 3, start the electric explosion device, control the transmission rate of the circulating micron aluminum powder to 8g / min, and complete the reaction under the conditions of a discharge voltage of 25KV, a capacitor capacity of 3.6μF, a discharge frequency of 0.5Hz, an electric explosion length of 100mm, and a deposition time of 50min, so that the nano aluminum powder particles produced by the electric explosion reaction are deposited on the micro aluminum powder particles circulating in the electric explosion chamber to obtain a micro-nano composite structure aluminum powder material. During the reaction, the consumption mass of the aluminum wire is 40g.

[0074] The prepared samples are collected to become micro-nano composite structure aluminum powder materials.

[0075] Application of the micro-nano composite structure aluminum powder material of the present invention:

[0076] The micro-nano composite structure aluminum powder material of the present invention can be used as a high-energy component for preparing solid rocket propellants or high-energy explosives.

[0077] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0078] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0079] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a micro-nano composite structure aluminum powder material, characterized in that: The method comprises the following steps: Step 1, fix the aluminum wire on the upper and lower electrodes in the electric explosion chamber; Step 2, feeding a formulated amount of micron aluminum powder into an electric explosion chamber, then evacuating the electric explosion chamber to a vacuum and filling it with argon gas, and adjusting the gas pressure to 0.1MPa-0.2MPa, so that the micron aluminum powder particles circulate in the electric explosion chamber; Step 3, starting the electric explosion device to deposit the nano aluminum powder particles generated by the electric explosion reaction on the micron aluminum powder particles circulating in the electric explosion chamber to obtain a micro-nano composite structure aluminum powder material; Wherein, in the micro-nano composite structure aluminum powder material, the mass ratio of micron aluminum powder to nano aluminum powder is (8-10):1; In the micro-nano composite structure aluminum powder material, the particle size distribution of nano aluminum powder particles is 100-200nm, and the particle size distribution of micron aluminum powder is 8-12μm; In step 1, the diameter of the aluminum wire is 0.1 to 0.35 mm; In the step 3, the transmission rate of the circulating micron aluminum powder is 4g / min to 10g / min; the discharge voltage of the electric explosion reaction is 20 to 30KV, the capacitor capacity is 3.0 to 4.0μF, the discharge frequency is 0.5 to 1.5Hz, and the electric explosion length is 70 to 120mm; the time for the nano aluminum powder particles to be deposited on the micro aluminum powder particles is 30 to 60min.

2. The method for preparing the micro-nano composite structure aluminum powder material according to claim 1, characterized in that: The shape of the micro-nano composite structure aluminum powder material is spherical, nearly spherical or quasi-spherical.

3. The method for preparing the micro-nano composite structure aluminum powder material according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1, fix the aluminum wire with a diameter of 0.2 mm on the upper and lower electrodes in the electric explosion chamber; Step 2, 300g of micron aluminum powder with an average particle size of 10μm is fed into the electric explosion chamber, and then the electric explosion chamber is evacuated to a vacuum and filled with argon gas, and the gas pressure is adjusted to 0.1MPa, so that the micron aluminum powder particles circulate in the electric explosion chamber; Step 3, starting the electric explosion device to deposit the nano aluminum powder particles generated by the electric explosion reaction on the micron aluminum powder particles circulating in the electric explosion chamber to obtain a micro-nano composite structure aluminum powder material; Wherein, in the micro-nano composite structure aluminum powder material, the mass ratio of micron aluminum powder to nano aluminum powder is 10:1; The particle size distribution of nano aluminum powder is 100-200nm; In the step 3, the transmission rate of the circulating micron aluminum powder is 5g / min; the discharge voltage of the electric explosion reaction is 25KV, the capacitor capacity is 3.6μF, the discharge frequency is 0.5Hz, and the electric explosion length is 100mm; the time for the nano aluminum powder to be deposited on the micro aluminum powder is 30min.

4. A micro-nano composite structure aluminum powder material, characterized in that: The composite material is prepared by the preparation method of the micro-nano composite structure aluminum powder material according to any one of claims 1 to 3.

5. The micro-nano composite structure aluminum powder material according to claim 4, characterized in that: In the micro-nano composite structure aluminum powder material, the mass ratio of micron aluminum powder to nano aluminum powder is 10:1; the particle size distribution of nano aluminum powder particles is 100-200 nm, and the particle size distribution of micron aluminum powder is 8-12 μm.

6. Use of the micro-nano composite structure aluminum powder material obtained by the preparation method of the micro-nano composite structure aluminum powder material as described in any one of claims 1 to 3 for preparing solid rocket propellants or high-energy explosives; or use of the micro-nano composite structure aluminum powder material as described in any one of claims 4 to 5 for preparing solid rocket propellants or high-energy explosives.

Citation Information

Patent Citations

  • Method and device for coated powder by electric explosion

    CN111922354A

  • Aluminum composite powders and preparation method thereof

    KR1020160052874A